Blood neuroexosomal excitatory amino acid transporter-2 is associated with cognitive decline in Parkinson’s disease with RBD - Leng, Bing; Sun, Hairong; Li, Mengfan; Zhao, Junwu; Liu, Xiaoxiao; Yao, Ran; Shen, Tengqun; Li, Zhenguang; Zhang, Jinbiao (Frontiers in Aging Neuroscience, 2022)
Background: Rapid eye movement (REM) sleep behavior disorder (RBD) predicts cognitive decline in Parkinson’s disease (PD) patients without dementia. However, underlying mechanisms remain unknown. Accumulating studies suggest glutamatergic system dysregulation is associated. Objective: To examine the effect of RBD on the rate of cognitive decline in early PD patients and investigate whether plasma levels of the neuroexosomal glutamate transporters VGLUT-1 and EAAT-2 are altered in PD patients with RBD. Methods: This study included 157 newly diagnosed treatment-naïve PD patients. Based on one-night polysomnography recordings, the subjects were divided into PD with RBD and PD without RBD groups. All participants received a complete evaluation of motor and nonmotor symptoms at baseline, which included evaluations of cognitive function and their psychiatric state. Plasma levels of neuroexosomal VGLUT-1 and EAAT-2 were measured by ELISA kits. After a three-year follow-up, we evaluated baseline plasma levels of neuroexosomal glutamate transporters in each group as a predictor of cognitive decline using MoCA score changes over three years in regression models. Results: A total of 157 PD patients completed the 3-year follow-up with complete serial assessments. Plasma levels of neuroexosomal EAAT-2 were significantly lower in PD patients with RBD at baseline. At the three-year follow-up, PD patients with RBD presented greater cognitive decline. Lower baseline blood neuroexosomal EAAT-2 predicted cognitive decline over 3 years in PD patients with RBD (β = 0.064, P = 0.003). Conclusion: These findings indicate that blood neuroexosomal EAAT-2 is associated with cognitive decline in early PD with RBD.